System level linear and non-linear modelling of RF/microwave integrated circuits for an antenna array receiver - Cheow, Cheng Wah (2008)
This Masters dissertation presents the research and development work of RF integrated circuits for an array antenna receiver, which will be employed in the base station for the MERLION LEO satellite transponder. The receiver operates under the Industrial, Scientific and Medical (ISM) scientific band at 2.4 to 2.5 GHz.